1991
DOI: 10.1353/aad.2012.1077
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Children's Implant Profile

Abstract: The decision to provide a child with a cochlear implant is quite complex, as it must include consideration not only of the implant itself but also of the habilitative services necessary following the surgical procedure. To provide a systematic means of selecting hearing-impaired children for cochlear implants, a team at Children's Hearing Institute, Manhattan Eye, Ear and Throat Hospital, developed the Children's Implant Profile (ChIP). There is no one profile of a successful implant user—at least 11 factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 1 publication
0
25
0
1
Order By: Relevance
“…4,5 The efficacy of multichannel cochlear implants for children with profound hearing loss has been well established, in terms of speech perception benefit, [6][7][8][9][10][11][12] language acquisition rates, [13][14][15] and speech production/intelligibility improvements. [16][17][18][19] Published research is now able to define the variables leading to optimum speech perception and language outcomes for children using the cochlear implant, such as younger age at implantation, [20][21][22][23][24][25][26][27] use of the most current speech processor technology, 28 a communication mode emphasizing an aural/oral approach, 10,29,30 absence of a developmental delay, 12,[31][32][33] shorter duration of profound hearing loss, 34 and preimplant residual hearing. [35][36][37] Based on outcomes and comparisons with hearing aid users, the application of implants has broadened to include children with a pure-tone average (PTA) in the range of 82 to 98 dB HL (hearing level).…”
Section: He First Cochlear Im-mentioning
confidence: 99%
“…4,5 The efficacy of multichannel cochlear implants for children with profound hearing loss has been well established, in terms of speech perception benefit, [6][7][8][9][10][11][12] language acquisition rates, [13][14][15] and speech production/intelligibility improvements. [16][17][18][19] Published research is now able to define the variables leading to optimum speech perception and language outcomes for children using the cochlear implant, such as younger age at implantation, [20][21][22][23][24][25][26][27] use of the most current speech processor technology, 28 a communication mode emphasizing an aural/oral approach, 10,29,30 absence of a developmental delay, 12,[31][32][33] shorter duration of profound hearing loss, 34 and preimplant residual hearing. [35][36][37] Based on outcomes and comparisons with hearing aid users, the application of implants has broadened to include children with a pure-tone average (PTA) in the range of 82 to 98 dB HL (hearing level).…”
Section: He First Cochlear Im-mentioning
confidence: 99%
“…A questionnaire and information form were developed from a compilation of sources (3,(5)(6)(7) and the combined experiences of a committee comprised of an otolaryngologist, an audiologist, an educational psychologist, and a teacher of students who are deaf and hard of hearing. Therapists at the clinic reviewed the questionnaire and made suggestions, which were incorporated into the final questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Value of Speech Development Level Assessment of the API Speech development level, which is also valuable for assessing the API, is an important criterion when selecting cochlear implant candidates [7][8][9] . Speech is acquired through learning after birth.…”
Section: Value Of Response To Environmental Sounds Assessment Of the Apimentioning
confidence: 99%
“…In 1989, Gantz [6] proposed medical and surgical criteria for cochlear implantation on adults and children. Hellman et al [7] reported the Children's Implant Profile (ChIP), which was used to systematically select the candidates for cochlear implantation. Since then, the ChIP or a variant of it has now been widely used by many cochlear implant centers [8,9] .…”
Section: Introductionmentioning
confidence: 99%